PROCESS OF MANAGEMENT OF VALUES IN SYSTEM OF FUNCTIONING OF companies - I. Musaelyan (Вестник университета)
Exactly today, when the set of the companies should fight for the segment, the product, service or even idea in the concrete market, high degree of relevance are got by a problem of influence of social methods of management on financial and economic aspects of activity of the companies. In the offered article, the special attention is paid to questions of valuable management of the companies, in part, formations of valuable reference points, and also determination of characteristics of process of valuable management. Article is executed within a state task of the Ministry of Education and Science of the Russian Federation.